African horse sickness: an ancient disease for a current threat - (:unkn) unknown (My University, 2022)
African horse sickness (AHS) is a major arthropod-borne disease that causes significant losses in horses in sub-Saharan Africa. It is caused by the African horse sickness virus (AHSV), which is transmitted during a blood meal by Culicoides biting midges. The distribution of historical African culicoid vectors increases due to global warming. In addition, recent (Thailand, 2020) and earlier (Iberian Peninsula, 1965-66/1987-90) AHS outbreaks outside Africa demonstrate the adaptation of the virus to endogenous species in AHS-free regions, similar to what has been observed for bluetongue disease in recent decades. Therefore, many regions are considered at risk of introduction of AHS which could have important economic consequences for the equine industry. Overall, this prone the European Union to launch research programs to get better diagnostic and prophylactic tools.
Keywords: African Research